A systematic review of pre-hospital shoulder reduction techniques for anterior shoulder dislocation and the effect on patient return to function - Fennelly, Joseph T.; Gourbault, Lysander; Neal-Smith, Gregory; Pradhan, Akhilesh; Gade, Venkat; Baxter, Jonathan A. (Chinese journal of traumatology, 2020)
The majority of acute anterior shoulder dislocations are sustained during sports and wilderness activities. The management of acute dislocations in the pre-hospital setting is currently without guidelines based on the evidence. The study aims to assess the risk of acute complications in pre-hospital shoulder reduction and identify which pre-hospital reduction technique has the highest success rate in the published literature. The involved databases were Allied and Complementary Medicine, CENTRAL, CINAHL, Cochrane Database of Systematic Reviews, Embase, Europe PMC, Ovid MEDLINE®, Pedro, Proquest, Trip, and World Health Organization International Clinical Trials Registry platform. Only original research of high methodological quality was included, which was defined by the recently developed assessment tool–assessing the methodological quality of published papers (AMQPP) and investigated the management of acute anterior shoulder dislocations in the pre-hospital setting. Two hundred and ninety-eight articles were identified and screened. A full text review was performed on 40 articles. Four articles published between 2015 and 2018 met the inclusion criteria. A total of 181 patients were included with the study duration ranging from 6 to 60 months. All studies reported zero immediate complication following pre-hospital reduction and there were no documented subsequent adverse events regardless of the technique used. Prompt resolution of neurological symptoms was observed following the early and successful pre-hospital reduction. First attempt success rate, when performed by skilled practitioners, ranged from 72.3% to 94.9%. Pre-hospital shoulder reduction appears to be a safe and feasible option when carried out with the appropriate expertise. A novel reduction technique adapted from the mountain medicine diploma course at the University of Paris North was found to have the highest first attempt reduction success rate of 94.9%. Other techniques described in the literature included Hippocratic, Stimson's, Counter-traction and external rotation with the success rates ranging from 54% to 71.7%.